2019
DOI: 10.5569/2340-5104.07.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Disfemia y ansiedad en el aprendizaje de inglés como lengua extranjera | Stuttering and anxiety in English as a foreign language learning

Abstract: Este trabajo fundamentalmente cualitativo explora la interrelación entre disfemia, ansiedad en una lengua extranjera (ALE), y aprendizaje de inglés para identificar las áreas de mayor dificultad de aprendizaje en estudiantes disfémicos adolescentes y adultos españoles aprendices de esta lengua. De una muestra de treinta y dos alumnos, dieciséis con disfemia (ACD) y dieciséis sin disfemia (ASD), se analizaron entrevistas realizadas con los primeros, y se compararon sus respuestas con las de los ASD a dos escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…On the other hand, negative emotions (e.g., boredom, anxiety, frustration) make it difficult to remember and may even inhibit remember since they make it difficult to fix the information in the memory and recover it for the task at hand, so learning is reduced rather than stimulated [8,9].Existing studies in the field of education, including foreign language learning, have shown that students' learning is related to emotions. Thus, negative emotions decrease academic performance, while positive emotions increase it [10,11]. However, studies to date have been based on specific emotions, ignoring the possible presence of other emotions that may have a significant influence on motivation and/or academic performance [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, negative emotions (e.g., boredom, anxiety, frustration) make it difficult to remember and may even inhibit remember since they make it difficult to fix the information in the memory and recover it for the task at hand, so learning is reduced rather than stimulated [8,9].Existing studies in the field of education, including foreign language learning, have shown that students' learning is related to emotions. Thus, negative emotions decrease academic performance, while positive emotions increase it [10,11]. However, studies to date have been based on specific emotions, ignoring the possible presence of other emotions that may have a significant influence on motivation and/or academic performance [12].…”
mentioning
confidence: 99%
“…Existing studies in the field of education, including foreign language learning, have shown that students' learning is related to emotions. Thus, negative emotions decrease academic performance, while positive emotions increase it [10,11]. However, studies to date have been based on specific emotions, ignoring the possible presence of other emotions that may have a significant influence on motivation and/or academic performance [12].…”
mentioning
confidence: 99%
“…This confirms the literature on FLCAS validation studies in both university and secondary students, validating the 4 factors and also reporting that the most perceived factor in the FLCAS is the fear of speaking or anxiety to communicate, with explained variance values for this factor between 35 to 38% and lower values for the other factors (Aida, 1994;Tóth, 2008;Arnaiz and Guillén, 2012;Jarie et al, 2019). Qualitative studies on English learning reinforce this result, showing that anxiety is the most significant variable in foreign language learning (Torres and Turner, 2017;García Pastor and Miller, 2019). The low variance value could have been affected by the sample or cultural factors.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, multiple researchers have shown that some situations which take place in the high school foreign language classroom such as speaking activities may cause stress and anxiety, intense emotions which hinder learning (Abreu 2016;Pastor & Miller, 2019). As highlighted by Champoux (1999) and Karadag (2009), since cinema contributes to re-ducing anxiety, it helps to create a friendlier and more stimulating learning environment.…”
Section: The Motivational Dimensionmentioning
confidence: 99%